Efektivitas Stretching PNF Setelah latihan Daya Tahan HIIT pada Atlet Cricket FIKK UNM - Mustamin, Nur Zalzabila; Hudain, Muh. Adnan; Mappanyukki, Andi Atssam; Ridwan, Andi; Ishak, Muhammad; Anwar, Khairil (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2026)
This study was conducted to examine the effect of Proprioceptive Neuromuscular Facilitation (PNF) stretching performed after High Intensity Interval Training (HIIT) on the recovery heart rate of cricket athletes at the Faculty of Sport and Health Sciences, Universitas Negeri Makassar. The research applied an experimental approach using a quasi-experimental design with a two-group pretest-posttest model. A total of 20 cricket athletes were selected through total sampling and assigned into experimental and control groups using the ordinal pairing technique. Recovery heart rate measurement after HIIT endurance training was utilized as the research instrument. Data analysis consisted of descriptive statistics, normality testing, homogeneity testing, and hypothesis testing using the t-test. The findings revealed that the application of PNF stretching following HIIT significantly reduced recovery heart rate, as indicated by a t-value higher than the critical t-table value and a significance level below 0.05. Therefore, PNF stretching can be considered an effective recovery strategy after high-intensity endurance training in cricket athletes.